IMPLEMENTASI PROGRAM LITERASI NUMERASI DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH DASAR - Ziara Aftira Zaulia; Lutfiah Hanum; Aldi Prasetyo (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
The study aims to know the implementation of literacy and numeration programs in college teaching the 7th generation and its effect on improving students' basic skills. The method used in this study is a descriptive qualitative with the subject of the study of 5th graders of the country's 2 chicken classes. Data is collected through observation, interview, and documentation, and analyzed using miles and huberman models. Research shows that literacy and numeration programs designed by students can enhance student learning motivation and have a positive effect on benefits from literacy. This is proven by an average increase in literacy value from 66% to 88% and numeration from 53% to 93% after implementation of the program. Thus, the implementation of a teaching college program has proved to be effective in supporting literacy and numeration capabilities in elementary schools.